THE PROBLEM OF INTERCULTURAL SPEACH IN TEACHING FOREIGN LANGUAGES AT TECHNICAL UNIVERSITIESY (Web of Teachers: Inderscience Research, 2025)
Currently, one of the progressively developing areas is intercultural communication. Globalization processes have forced linguists, philologists and teachers to pay special attention to such an aspect of communication as interaction in an intercultural environment and the teaching of foreign languages, between which there is a close connection. The article discusses issues of intercultural communication in teaching foreign languages.